The effect of research laboratories in improving classroom research for high school students in the city of Dawadmi / K.S.A - Alotibe, Wafa Mohmad Mobark (Journal of Educational and Psychological Sciences, 2021)
This study aimed to demonstrate the effect of research laboratories on improving classroom research for high school students in the city of Dawadmi in the Kingdom of Saudi Arabia for the year (1441-1442), and the researcher followed the descriptive analytical method for its relevance to the nature of this study, and a questionnaire was applied to an intentional sample that included (150) students In secondary schools in the city of Dawadmi, the results of the study revealed that the general tool obtained an overall average (3.32 out of 5) with a grade of (average) and at the level of the axes, the axis of impact obtained an overall average (3.43), while the reality of scientific research axis obtained an overall average (3.21 out of 5) And both of them are of verbal estimation (average), and the results also showed that there are no statistically significant differences at the level of (α≤0.05) between the sample answers according to the study variables (school location, specialization). Improving classroom research by establishing and qualifying research laboratories in Saudi schools and at various educational levels to train students in scientific and electronic research and information awareness (information security).